Development of the algorithm and structure of software for diagnostics of mobile power facilities - D. V. Kazakov; N. L. Gurzhi; N. E. Kurdagia (Омский научный вестник)
The paper develops an algorithm for determining the required diagnostic parameters and performance indicators of mobile power equipment (MPE), which implements the methodology improved by the authors of the non-brake studies of the internal combustion engine (ICE) and moving MPE during the transient process of their acceleration. For the first time, the regularity of recording, processing data from primary converters and the sequence of calculating model parameters is shown, with the possibility of taking into account the characteristics of the transient processes of acceleration of the crankshaft of the internal combustion engine and the MPE, Thus, the developed algorithm and software structure are able to implement the methodology proposed by the authors of the non-standard studies of the internal combustion engine (ICE) and the moving MPE. To fix the required parameters from the primary converters, it is proposed to use the well-known programs CoolEdit2000 v.1.0.2374 and VisualGPS v.4.2.105.1. The article describes in detail each process of the algorithm, reflects the procedure for working with primary information and ways to improve the accuracy of calculations.